2019
DOI: 10.1101/642298
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Extensive Transcriptional and Translational Regulation Occur During the Maturation of Malaria Parasite Sporozoites

Abstract: 22 Introduction: 41Malaria remains one of the great global health problems today, taking a large toll on people in the 42 tropics and subtropics. This disease, caused by Plasmodium parasites, affects over 200 million people 43 annually and kills over 400,000 (WHO World Malaria Report 2018). While a protein-based subunit 44 vaccine (RTS,S) has recently been licensed and is being used for pilot implementation in three Saharan African countries, its protection has been limited and relatively short-lived in clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 81 publications
2
7
0
Order By: Relevance
“…SPATR is a conserved protein with adhesive domains expressed in all invasive stages of Plasmodium. Despite the upregulation of transcription in infectious sporozoites, we found that SPATR is, as previously described, essential for the asexual blood stages (12,15,19).…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…SPATR is a conserved protein with adhesive domains expressed in all invasive stages of Plasmodium. Despite the upregulation of transcription in infectious sporozoites, we found that SPATR is, as previously described, essential for the asexual blood stages (12,15,19).…”
Section: Discussionsupporting
confidence: 78%
“…Moreover, maximum excision of the target locus is only achieved upon a temperature switch, which is usually performed once sporozoites are already present in the salivary glands, as the rise in temperature leads to the blockage of salivary gland colonization (63). Since spatr starts being transcribed in oocysts and is then subjected to translational repression (15), this creates a temporal window for sporozoites to produce and store mRNA that can be translated even after the recombination event. Therefore, the study of the importance of genes for the mosquito phase of the life cycle of the parasite using the Flp-FRT system may have additional limitations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, Articles NATURe MICRObIOlOgY P. falciparum encodes only two YTH proteins, and while their roles are unknown, the divergence of these two proteins beyond their YTH domain and the distinct expression patterns during the parasite lifecycle suggest that they mediate two distinct functions. m 6 A has not been associated with translational repression in any eukaryote yet, but this post-transcriptional regulation is of particular importance for P. falciparum during the IDC 15 and especially during transmission between the human host and mosquito vector 47,48 . During the latent gametocyte and salivary gland sporozoite stages, mRNAs are kept in a translationally repressed state and protein synthesis is only initiated following transmission, readily ensuring rapid continuation of development 12,49 .…”
Section: Nature Microbiologymentioning
confidence: 97%